Patterns of dispensed opioids after tonsillectomy in children and adolescents in South Carolina, United States, 2010–2017 - Basco, William T.; Ward, Ralph C.; Taber, David J.; Simpson, Kit N.; Gebregziabher, Mulugeta; Cina, Robert A.; McCauley, Jenna L.; Lockett, Mark A.; Moran, William P.; Mauldin, Patrick D.; Ball, Sarah J. (International journal of pediatric otorhinolaryngology, 2021)
Tonsillectomy (with or without adenoidectomy) is a common pediatric surgical procedure requiring post-operative analgesia. Because of the respiratory depression effects of opioids, clinicians strive to limit the use of these drugs for analgesia post-tonsillectomy. The objective of this study was to identify demographic and medication use patterns predictive of persistent opioid dispensing (as a proxy for opioid use) to pediatric patients post-tonsillectomy. Retrospective cohort of South Carolina (USA) Medicaid-insured children and adolescents 0–18 years old without malignancy who had tonsillectomy in 2014–2017. We evaluated opioid dispensing pre-surgery and in the 30 days exposure period after hospital discharge. The main outcome, persistent opioid dispensing, was defined as any subject dispensed ≥1 opioid prescription 90–270 days after discharge. Group-based trajectory analyses described post-procedure opioid dispensing trajectories. There were 11,578 subjects representing 12,063 tonsillectomy procedures. Few (3.5%) procedures were followed by persistent opioid dispensing. Any opioid dispensing during the exposure period was associated with an increased odds of persistent opioid dispensing status during the follow up period (OR 1.51 for 1–6 days of exposure and OR 1.65 for 7–30 days of opioid exposure), as was pre-procedure opioid dispensing, having >1 tonsillectomy procedure, and having complex chronic medical conditions. Group-based trajectory analyses identified 4 distinct patterns of post-discharge opioid dispensing. Any opioid dispensing during the 30 days after tonsillectomy increased the odds of persistent opioid dispensing by > 50%. Multivariable and group-based trajectory analyses identified patient and procedure variables that correlate with persistent opioid dispensing, primarily driven by groups receiving pre-tonsillectomy opioids and a second group who experienced multiple episodes of tonsillectomy. •Any opioid dispensing in the 30 days after tonsillectomy increased odds of persistent opioid dispensing.•Risk factors for persistent dispensing include pre-surgical opioid dispensing and patient characteristics.•Clinicians can identify patients at risk for persistent opioid dispensing and devise care plans accordingly.